The Association between Breast Cup Size and Breast Cancer Incidence: Insights from a Global Dataset - Faraz, Mehdi; Nematollahi, Samaneh; Tahmasebi, Sedigheh; Welsh, James S; Bevelacqua, Joseph John; Mortazavi; Seyed Mohammad Javad; Mortazavi, Seyed Alireza (Shiraz University of Medical Sciences, 2025)
The relationship between breast size and breast cancer risk is complex and not fully understood. This study investigates how breast size, categorized by cup size, correlates with age-standardized rates (ASR) of breast cancer incidence. Data were collected from two sources: breast cancer incidence rates from the Global Cancer Observatory (GCO) and breast size data from "Data Pandas," an open-access database. This allowed for a cross-country analysis of breast cancer incidence and breast size characteristics. Descriptive statistics indicated that ASR increased with larger cup sizes, ranging from 34.72 (AA) to 90.17 (C). An ANOVA test revealed significant differences in mean ASR among cup size groups (F=14.416, P<0.001), with Bonferroni comparisons showing distinct clusters: smaller sizes (AA, AA-A, A) differed significantly from larger sizes (A-B, B, B-C, C).The largest mean ASR difference was between groups A and C (-42.93, P=0.001), highlighting higher ASR in larger cup sizes. This suggests a significant association between breast cup size and breast cancer ASR, potentially linked to physiological or hormonal factors.Despite limitations, these findings prompt further investigation. The next phase will focus on breast cancer patients, addressing relevant risk factors for a more comprehensive understanding of the associations observed.